Dissecting the Role of Promoters of Pathogen-sensitive Genes in Plant Defense - Baruah, Indrani; Baldodiya, Gajendra M.; Sahu, Jagajjit; Baruah, Geetanjali (Current Genomics, 2020)
Plants inherently show resistance to pathogen attack but are susceptible to multiple bacteria, viruses, fungi, and phytoplasmas. Diseases as a result of such infection leads to the deterioration of crop yield. Several pathogen-sensitive gene activities, promoters of such genes, associated transcription factors, and promoter elements responsible for crosstalk between the defense signaling pathways are involved in plant resistance towards a pathogen. Still, only a handful of genes and their promoters related to plant resistance have been identified to date. Such pathogen-sensitive promoters are accountable for elevating the transcriptional activity of certain genes in response to infection. Also, a suitable promoter is a key to devising successful crop improvement strategies as it ensures the optimum expression of the required transgene. The study of the promoters also helps in mining more details about the transcription factors controlling their activities and helps to unveil the involvement of new genes in the pathogen response. Therefore, the only way out to formulate new solutions is by analyzing the molecular aspects of these promoters in detail. In this review, we provided an overview of the promoter motifs and cis-regulatory elements having specific roles in pathogen attack response. To elaborate on the importance and get a vivid picture of the pathogen-sensitive promoter sequences, the key motifs and promoter elements were analyzed with the help of PlantCare and interpreted with available literature. This review intends to provide useful information for reconstructing the gene networks underlying the resistance of plants against pathogens.
Keywords: pathogen resistance